THE EFFECT OF ETHICAL LEADERSHIP ON EMPLOYEE PERFORMANCE AND INCREMENTAL INNOVATION WITH INTERNAL MOTIVATION AS AN INTERVENING VARIABLE IN THE DISTRICT LIBRARY AND ARCHIVES DEPARTMENT DELI SERDANG - Budi Alamsyah Siregar; Ahmad Ibrahim Nasution (Strategic Management Business Journal, 2023)
Technological changes are so fast, putting leaders under pressure. The purpose of this research is to partially determine the effect of ethical leadership and internal motivation on employee performance. To determine the effect of ethical leadership on internal motivation. To determine the effect of ethical leadership on incremental innovation. The results of the study show that ethical leadership has a significant effect on internal motivation as indicated by the results of Sig. (0.001 <0.05). Ethical leadership has a significant effect on employee performance with Sig. (0.010 <0.05). Ethical leadership has a significant effect on incremental innovation as indicated by the results of Sig. (0.009 <0.05). Internal motivation has no effect on employee performance as indicated by the results of Sig. (0.795 > 0.05). Internal motivation has a significant effect on incremental innovation as indicated by the results of Sig. (0.002 <0.05). Ethical leadership has no effect on employee performance through internal motivation as shown by the results of Sig. (0.871 > 0.05). Ethical leadership has no effect on incremental innovation through internal motivation as shown by the results of Sig. (0.896 > 0.05). JEL Classification: L21, L25